2021
DOI: 10.1002/nop2.1023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a group‐walking intervention for people with dementia based on quality of life and caregivers’ burden

Abstract: According to the World Health Organization (WHO), around 50 million people worldwide have dementia, and there are nearly 10 million new cases every year (World Health Organization, 2017a). ICD-10 defines dementia as "a syndrome due to disease of the brain, usually of a chronic or progressive nature, in which there is a disturbance of multiple higher cortical function, including memory, thinking, orientation, comprehension, calculation, learning capacity, language and judgement" (World Health Organization, 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 28 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…21 Studies included in this review showed that such interventions to enrich the care for OPD are feasible for implementing with volunteers as non-professionals. [12][13][14][15][16] This result aligns with a previous study by Luger et al that reported the impact of volunteers conducting home-based physical training, nutritional, and social support for older persons living at home. In addition, the assistance from volunteers could help overcome malnutrition status and frailty, and decrease isolation and loneliness in older people.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…21 Studies included in this review showed that such interventions to enrich the care for OPD are feasible for implementing with volunteers as non-professionals. [12][13][14][15][16] This result aligns with a previous study by Luger et al that reported the impact of volunteers conducting home-based physical training, nutritional, and social support for older persons living at home. In addition, the assistance from volunteers could help overcome malnutrition status and frailty, and decrease isolation and loneliness in older people.…”
Section: Discussionsupporting
confidence: 91%
“…17,18 In home or community-based settings, through programs with trained volunteers, patients and their caregivers were encouraged to engage in social activities and enabled to build a relationship with either the volunteers or even with other participants if it was a group program. 12,13,15 Interventions accompanied by trained volunteers were shown to decrease loneliness, and improve mood and social connectedness, moreover affecting the physical and mental well-being of OPD positively. 12,14 Related to psychosocial interventions in dementia care, Chirico et al (2021) found that psychosocial interventions enable people with dementia to maintain their independence and functional ability, reduce behavioural and psychological symptoms, and enrich their quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations